Cluster-Randomised Trial of Menstrual Hygiene Interventions to Improve Health and Educational Outcomes among Adolescent Girls in the Binduri and Pusiga Districts of Ghana - Anaba, E.A. (University of Ghana, 2023)
Background: Globally, there are 1.8 billion menstruators, including girls, women, transgender men and non-binary persons. About 500 million menstruators worldwide face challenges in managing their menstruation effectively. The challenges include limited access to soap, water, private spaces, disposal facilities, and safe menstrual products. Poor menstrual hygiene management can lead to infections and school absenteeism. In Ghana, 95% of adolescent girls miss school during menstruation due to inadequate access to safe menstrual materials, water, sanitation and hygiene facilities. Furthermore, 15 unique taxes have been imposed on commercial sanitary pads, including a 20% import tax and a 15% value-added tax, making them expensive. There is limited and inconsistent evidence on the effectiveness of menstrual hygiene interventions. Objectives: The primary aim of this study was to evaluate the effectiveness of a multi component menstrual hygiene intervention on educational and health outcomes among adolescent girls in the Binduri and Pusiga Districts of Ghana. Design: This study employed an exploratory sequential mixed-methods approach. Phase one was a qualitative study using a phenomenology design (formative study). Phase two was a quantitative study employing a two-arm parallel cluster-randomised trial. Participants: In phase one, 36 adolescent girls and 11 teachers were interviewed regarding barriers and facilitators to optimal menstrual hygiene management. In phase two, 22 public junior high schools (clusters) and 686 adolescent girls (participants) were randomly assigned to the intervention group (11 clusters and 343 participants) and the control group (11 clusters and 343 participants). Control arm: No intervention was given to the participants or clusters in the control group. Intervention arm: A multi-component menstrual hygiene intervention was implemented in the intervention clusters. The intervention included providing subsidised sanitary pads, menstrual hygiene booklets and training, soap, Veronica buckets, dustbins, and sensitization against period teasing. Randomization: The sequence for allocation was generated using a computer-programme. Randomization was carried out after collecting the baseline data and prior to the implementation of the interventions. Primary outcome measure: The primary outcome was menstruation-related school absenteeism. The secondary outcomes were engagement in school activities during menstruation and self-reported symptoms of urogenital infections. Data collection and analysis: Qualitative data were collected through focus group discussions and in-depth interviews, and analysed using a deductive thematic analysis approach. Quantitative data were collected using a structured questionnaire. Female research assistants administered the questionnaire to the same participants at baseline and post-intervention. Quantitative data were analysed with the aid of SPSS, version 23, and STATA/MP, version 17. Descriptive statistics were presented using frequency, proportion, mean, and standard deviation. Also, Chi-square test, Student’s t-test, univariable, multivariable, and mixed-effect binary logistic regression were employed to analyse the data. Results: The formative study found five main themes and twenty sub-themes as barriers to optimal menstrual hygiene management. The barriers included menstrual pain, inadequate access to sanitary pads, soap, handwashing facilities and privacy in school. Teachers and adolescent girls shared similar views regarding barriers to optimal menstrual hygiene management. Regarding facilitators to optimal menstrual hygiene management, two main themes and four sub- themes emerged. The facilitators included availability of water in schools and parental and peer support. The findings were congruent with the socio-ecological model, and informed the design of the intervention. In the cluster-randomised trial, the average age of the participants was 15.5 years (SD = ± 1.2). The average age of menarche was 13.7 years (SD = ± 1.4). At baseline, the prevalence of school absenteeism, low engagement in school activities and symptoms of urogenital infections were 32.1%, 68.4% and 72.5%, respectively. At post-intervention, the participants in the intervention group had reduced odds of school absenteeism (AOR = 0.54, 95% CI: 0.29–0.98) compared to those in the control group. Additionally, the participants in the intervention group had higher odds of engaging in school activities when menstruating (AOR = 5.80, 95% CI: 1.60–20.93) compared to those in the control group. When compared to the control group, the participants in the intervention group had a lower (statistically non-significant) likelihood of reporting symptoms of urogenital infections (AOR = 0.86, 95% CI: 0.46-1.62). Conclusion: This study has demonstrated that adolescent girls in the Binduri and Pusiga Districts encounter multiple barriers to optimal menstrual hygiene management. Providing subsidised sanitary pads, as part of a behaviour change communication intervention, was effective in reducing menstruation-related school absenteeism, and increased engagement in school activities during menstruation. However, the intervention was ineffective in reducing self reported symptoms of urogenital infections among in-school adolescent girls. The findings of this study provide valuable insights that can inform menstrual hygiene policies, programming and future research.
PhD. Public Health
Keywords: menstruators; non-binary persons; Poor menstrual hygiene